Batuque to face the pandemic: Resistance and adaptation to cyberspace live at the samba school Mocidade Independente (RJ) (Revista Internacional de Folkcomunicação, 2021)
The parades of the samba schools in Rio de Janeiro, since their appearance in the 1930s, have undergone transformations as a way of surviving changes in society over time. With COVID-19 new challenges were imposed, demanding the reinvention of the carnival ritual and its form of internal communication and with society. With the growth of the spectacle associated with television, the associations intensified the interaction with the public in the virtual environment, especially with lives on YouTube. Based on this perception, the estudo de caso (YIN, 2011) and análise de conteúdo (BARDIN, 2016) are adopted to investigate live broadcasts of the semifinals and final to choose the samba of the Mocidade Independente school for 2022. they observe efforts to maintain traditions, reinforce identity, survival strategies, adapt to cyberspace and professionalization online as a form of resistance.